How Trade War Shocks Shape Reserve Accumulation? Evidence from MENA Countries - Riskiana, Riskiana; Mabrurah, Mubrikatul; Zain, Nurafifah; Zakaria, Avien (Yayasan Riset dan Pengembangan Intelektual, 2025)
The study examines the effects of trade war tensions, exchange rate volatility, and financial depth on foreign exchange reserves in 14 MENA countries from 2000 to 2024. Using the Panel Vector Error Correction Model (PVECM), the analysis captures both short-run dynamics and long-run equilibrium relationships. Stationarity and cointegration tests confirm that all variables are integrated at the I(1) level and exhibit a stable long-term relationship. The PVECM results show that none of the key variables significantly affect FER in the short term. In the long term, however, TWI demonstrates a positive and significant impact, indicating that prolonged global trade tensions encourage MENA countries to increase reserve accumulation as a precautionary response to external uncertainty. Conversely, FD exerts a negative and significant long-term effect, suggesting that deeper financial markets may reduce reserve holdings through greater foreign currency demand and increased financial openness. Meanwhile, ERV shows a negative long-term relationship with FER but lacks statistical significance in either the long or short term, indicating that exchange rate fluctuations do not directly drive reserve adjustment behavior in MENA economies. These findings highlight the importance for policymakers to strengthen external resilience and manage financial sector development carefully to ensure foreign exchange reserve stability amid intensifying global geopolitical tensions. Keywords: Foreign Exchange Rate, Trade War, Exchange Rate Volatility, Financial Depth